Advanced image processing techniques and applications - Nafarajan, Suresh Kumar; Sangaiah, Arun Kumar 1981-; Arun, M. 1979-; Anand, S. (Advances in computational intelligence and robotics (ACIR) book series, 2017)
"[This book] is an essential reference publication for the latest research on digital image processing advancements. Featuring expansive coverage on a broad range of topics and perspectives, such as image and video steganography, pattern recognition, and artificial vision, this publication is ideally designed for scientists, professionals, researchers, and academicians seeking current research on solutions for new challenges in image processing" - Provided by publisher